The growth of patient autonomy in modern medical practice and the defined limitations under the Shariah - Jahn Kassim, Puteri Nemie; Alias, Fadhlina; Wan Muhammad, Ramizah (2014)
The concept of patient autonomy or self-determination is one of the dominant ethos in modern medical practice. The demands by patients to be given respect, independence and dignity in medical decision making have been heeded and mirrored in many ethical codes and judicial decisions. The development of the law relating to informed consent, euthanasia, confidentiality, and reproduction issues have clearly reflected the reinforcement of patient autonomy in which patients’ choices should be free from coercion and unwanted interference. Paternalistic infringement in these areas have been regarded as outmoded and are disfavoured, as respect for a patient’s right to determine his own destiny is given precedence. The escalating medico-legal cases have further emphasised the salience of this concept in the provision of medical services. Nevertheless, while the importance of patient autonomy is duly recognised, the advancement of this concept is not without its limitations; it accordingly has to evolve within the perimeters of one’s religious and cultural precepts. For Muslim patients, the right and ability to make their own choices and decisions about medical care and treatment must be within the defined limitations of the Shari’ah. The emphasis on individualism, personal gratification and the denial of faith in medical decision making is inconsistent with Islamic values. Therefore it is necessary that principles relating to the concept of patient autonomy be developed within the sphere of the Shari’ah, in order to ensure their coherence with the doctrinal requirements stipulated in Islam.